2018
DOI: 10.31887/dcns.2018.20.3/ccarvajal
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder as a diagnostic entity – clinical perspectives

Abstract: Throughout history the consequences of psychological trauma and characteristic symptoms have involved clinical presentations that have had different names. Since the inclusion of the category of Posttraumatic Stress Disorder (PTSD) in the third edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-III) with the symptomatic triad of re-experiencing the traumatic event, avoidance behaviors, and hypervigilance, this entity has been a source of controversy. Indeed, some authors have denied its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(44 reference statements)
1
10
0
1
Order By: Relevance
“…In contrast, anxiety is a response to potential threats and is operationally defined as avoidance of potential risks involving open spaces, bright lights, and novel conspecifics ( Steimer, 2002 ; LeDoux, 2015 ). An association between stress and anxiety is well-established ( Shin and Liberzon, 2010 ; Bystritsky and Kronemyer, 2014 ; Daviu et al, 2019 ) with stress being a contributing factor for most anxiety disorders including social anxiety disorder and posttraumatic stress disorder (PTSD) ( Bystritsky and Kronemyer, 2014 ; Carvajal, 2018 ). The causal relationship between stress and anxiety is most dramatically exemplified by PTSD where a single but intensely stressful experience can lead to a long-lasting anxiety state in susceptible individuals ( Nemeroff et al, 2006 ; Craske and Stein, 2016 ).…”
Section: Stress and Anxietymentioning
confidence: 99%
“…In contrast, anxiety is a response to potential threats and is operationally defined as avoidance of potential risks involving open spaces, bright lights, and novel conspecifics ( Steimer, 2002 ; LeDoux, 2015 ). An association between stress and anxiety is well-established ( Shin and Liberzon, 2010 ; Bystritsky and Kronemyer, 2014 ; Daviu et al, 2019 ) with stress being a contributing factor for most anxiety disorders including social anxiety disorder and posttraumatic stress disorder (PTSD) ( Bystritsky and Kronemyer, 2014 ; Carvajal, 2018 ). The causal relationship between stress and anxiety is most dramatically exemplified by PTSD where a single but intensely stressful experience can lead to a long-lasting anxiety state in susceptible individuals ( Nemeroff et al, 2006 ; Craske and Stein, 2016 ).…”
Section: Stress and Anxietymentioning
confidence: 99%
“…However, an emerging and broader view suggests that PTSD is a systemic metabolic disorder “in disguise” (Bukhbinder & Schulz, 2016; Michopoulos et al, 2016), involving CNS, neuroendocrine, metabolic, and inflammatory elements (Carvajal, 2018; Flory & Yehuda, 2018; McFarlane, 2017; Mellon et al, 2018; Michopoulos et al, 2016). This alternate perspective suggests that PTSD be reconceptualized as broader than a psychological disorder (McFarlane, 2017; Michopoulos et al, 2016).…”
mentioning
confidence: 99%
“…A systematic review conducted by Jellestad et al ( 23 ) found PTSD has been associated with impairment in the ICF domains of “General Tasks and Demands, Mobility, Self-Care, Domestic Life, Interpersonal Interactions and Relationships, Major Life Areas and Community, Social and Civic Life” (p. 14). The DSM III criteria for PTSD was based on dysfunctions in three domains: hypervigilance, the re-experiencing of the original trauma, and avoidant behavior of stimuli associated with the original trauma ( 24 ). In 1994, the DSM IV revised and expanded the diagnostic criteria for PTSD, which were subsequently widely criticized for reasons as disparate and contradictory as being too narrow in defining trauma to being over-diagnosed and thus too sensitive in populations recently exposed to traumatic events ( 25 , 26 ).…”
Section: Ptsdmentioning
confidence: 99%